Basic measurements of radiation at station Southern Great Plains (1994-01 et seq) - Laura Riihimaki; Gary Hodges (PANGAEA, 2024)
This is a compilation of all short-wave and long-wave radiation datasets from the U.S. Department of Energy Atmospheric Radiation Measurement (ARM) run station Southern Great Plains that were and are published in the frame of BSRN. New data will be added regularly.